Correction: Nutritional markers and proteome in patients undergoing treatment for pulmonary tuberculosis differ by geographic region - Jarlsberg, Leah G.; Kedia, Komal; Wendler, Jason; Wright, Aaron T.; Piehowski, Paul D.; Gritsenko, Marina A.; Shi, Tujin; Lewinsohn, David M.; Sigal, George B.; Weiner, Marc H.; Smith, Richard D.; Keane, Joseph; et al. (PloS one, 2025)
[This corrects the article DOI: 10.1371/journal.pone.0250586.].